Evaluasi Harga Saham Perusahaan Asuransi Selama Era Pandemi di Indonesia: Apakah Earnings Per Share Penting? - Nitri Mirosea; Iffat Al-Tho’riq Kusnan; Yuli Lestari Labangu (Society, 2022)
A corporation with excellent financial performance will affect the stock demand and prices. Data shows that the average stock price from 2017 to 2020 decreased by 268.07 points, and only three of the nine insurance companies showed above-average market prices. From 2017 to 2020, this research will look at how book value per share and earnings per share influence the stock price of IDX-listed insurance businesses. The sample for this study consists of nine insurance companies concluded on the IDX, as determined by a set of criteria. The study used multiple linear regression analysis methods. The study concluded as follows: (1) Partial earnings per share did not significantly affect stock prices; (2) The insurance company’s stock price is significantly impacted by partial book value per share; and (3) Book value per share and earnings per share have substantial effect on stock prices.